Bleeding with anticoagulant treatments - Palareti, G. (Hämostaseologie, 2011)
Anticoagulation with vitamin K antagonists (VKAs) is effective in the prevention and treatment of thrombotic complications in many clinical conditions, including atrial fibrillation (that represents today the most frequent indication for anticoagulant treatment), venous thromboembolism, acute coronary syndromes and after invasive cardiac procedures. Bleeding is the most important complication of VKAs and a major concern for both physicians and patients, limiting a more widespread prescription of the treatment. As a result, a non negligible proportion of all the subjects who would have a clear clinical indication for anticoagulation do not receive an effective treatment.This review analyses the treatment- and person-associated risk factors for bleeding during VKAs. New oral anticoagulant drugs seems to overcome at least some of the limitations of VKAs. Potentially, they can allow a less demanding and more stable anticoagulant treatment, with less side-effects allowing that more patients can receive an appropriate anticoagulant treatment. Based on the so far available phase III clinical studies, it is possible to assume that these new drugs are associated with a risk of bleeding, that is probably related to the intensity of treatment.
Keywords: Anticoagulation; vitamin K antagonists; bleeding; new oral anticoagulants